The Effects of Perfluoroalkyl Compounds on In Ovo Toxicity and Hepatic mRNA Expression in the Domestic Chicken (Gallus gallus domesticus) - O'Brien, Jason (Université d'Ottawa / University of Ottawa, 2011)
Perfluoroalkyl compounds (PFCs) are a group of chemical surfactants most notably used in non-stick and stain-resistance applications. Due to their wide-spread use and inherent resistance to degradation, several PFCs have become persistent environmental contaminants. Despite the high concentrations of PFCs reported in wild birds and their eggs, very little is known about the toxicological effects they have on avian species. This thesis investigates the developmental toxicity of PFCs in an avian model species: the domestic chicken (Gallus gallus domesticus). Egg injection experiments were performed to assess the in ovo toxicity of perfluorooctane sulfonate (technical grade, T-PFOS), perfluorooctanoic acid (PFOA), perfluorodecane sulfonate (PFDS) and perfluoroundecanoic acid (PFUdA). Real-time RT-PCR was then used to measure the transcription of candidate biomarker genes in the liver tissue of day 20 embryos. Candidate genes were selected based on their responsiveness to PFC exposure in previously conducted in vitro screening assays. In ovo exposure to PFOS resulted in a dose-dependent decrease in embryo pipping success (a measure of hatching success) with an LD50 of 93 μg/g (3.54 μg/g-672,910 μg/g, 95% confidence interval), however the expression of peroxisome proliferator-activated receptor alpha (PPARα)-regulated genes was not affected in liver tissue as hypothesized. PFOA, PFDS and PFUdA had no effect on the pipping success of chicken embryos. The expression of cytochrome P450 1A4 (CYP1A4) and liver fatty acid binding protein (L-FABP) mRNA increased in embryo liver tissue following in ovo exposure to PFUdA but was only statistically significant at 10 μg/g, which is several orders of magnitude higher than concentrations reported in wild bird eggs. The isomer-specific accumulation of PFOS in chicken embryo livers was also investigated using an in-port derivatization gas-chromatography/mass spectrometry (GC-MS) method. Prior to incubation, chicken eggs were injected with T-PFOS, composed of 63% linear isomer (L-PFOS) and 37.3% branched isomers. The isomer profiles in day-20 embryo liver tissue showed up to 20% enrichment in the proportion of L-PFOS, compared to T-PFOS, with a corresponding decrease in the proportion of branched isomers. This enrichment was inversely proportional to dose. Finally, the transcriptional profiles of cultured chicken embryonic hepatocytes (CEH) exposed to either T-PFOS or L-PFOS were compared using Agilent 4x44k Chicken (V2) Gene Expression microarrays. At equal concentrations (10 μM), T-PFOS altered the expression of significantly more genes (340 genes, >1.5 fold change, false discovery rate adjusted p<0.05) compared to L-PFOS (130 genes). Functional analysis showed that L-PFOS and T-PFOS affected genes involved in lipid metabolism, cellular growth and proliferation, and cell-cell signaling. Pathway and interactome analysis suggested that gene expression may be affected through RXR, oxidative stress response, TP53 signaling, MYC signaling, Wnt/β-catenin signaling and PPARγ and SREBP receptors. In all functional categories and pathways examined, T-PFOS had a more pronounced disruptive effect on transctional regulation than L-PFOS. In summary, egg injection experiments showed that T-PFOS (but not linear PFOA, PFDS or PFUdA) may affect the hatching success of the chicken at environmentally relevant concentrations. It was also demonstrated that the accumulation of PFOS in embryonic liver is isomer specific, and leads to an enrichment of L-PFOS. The increased transcriptional disruption caused by T-PFOS in cultured hepatocytes over L-PFOS suggests that the branched isomers may be largely responsible for the toxicological effects of PFOS. Combined, the results from this thesis demonstrate the importance of considering PFOS isomer burdens during risk assessment. In addition, gene expression analysis identified several candidate mechanisms for PFOS toxicity.
Keywords: PFC; PFAA; perfluoroalkyl compounds; perfluoroalkyl acids; Chicken; avian; toxicology; egg injection; gene expression; microarray; PFOS; PFOA; PFUdA; PFDS; perfluorooctanoic acid; perfluorooctane sulfonate; isomer